ANALISIS JALUR HUBUNGAN DURASI TIDUR DAN ASUPAN PROTEIN PADA IBU HAMIL ANEMIA DENGAN KEJADIAN BERAT BAYI LAHIR RENDAH - Fitriani, Sufia; Pamungkasari, Eti Poncorini; Suminah, Suminah (GIZI INDONESIA, 2019)
Anemia is highly prevalent among Indonesian community, especially in pregnant women. Sleep duration and poor sleep patterns when someone is pregnant mayincrease therisk factors that affect the outcome of pregnancy. Protein requirements for pregnant women will increase as increasing gestational age. Lack of protein intake maycause low birth weight.The purpose of this study was to analyze the correlationof sleeping duration and protein intake in anemic pregnant women with the incidence of low birth weight babies.The study used a case control design. The subject of the study was anemic pregnant women in Sukoharjo who have been gaving birth from 2016 to 2018. Subjects wereselected using purposive sampling. Case was those who delivered normal baby?s weight and case was those who delivered low bird weight baby. 74 subjcts were in control group and 37 subjects were in case group.Sleeping duration was measured during sleep at night per hour and the quality of sleeping using PSQI from. Path analysiswasused to evaluate the association.The results showed that the association of sleeping duration of anemic pregnant women with incidence of LBW was not significant (p=0,285); protein intake withincidence of LBW was significant (p=0,019), and sleep quality anemic pregnant women with incidence of LBW was not significant (p=0,379). There is no significant direct and indirect associations (through sleep quality) of sleeping duration among anemic pregnant women withincidence of LBW, there is a significant associationof protein intake in anemic pregnant women with incidence of LBW, and there is no significant indirect association (through sleep quality) of protein intake in anemic pregnant women with incidence of LBW babies.